2020
DOI: 10.4103/ijpsym.ijpsym_320_19
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Matrix Metalloproteinase-9 and Lifetime History of Suicidal Behavior in Remitted Patients with Bipolar I Disorder: A Cross-Sectional Pilot Study

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It suggested the role of biomarkers, especially in suicidality in bipolar disorder. [ 18 ] A study by Goyal et al [ 19 ] was done on a total of 120 subjects on inflammatory markers in the first episode and bipolar mania. The results of the study supported the inflammatory pathophysiology of mania as shown by significantly higher values of neutrophil counts and neutrophil/lymphocyte ratio (NLR) and significantly lower values of lymphocyte counts in both the first episode and bipolar mania compared to healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested the role of biomarkers, especially in suicidality in bipolar disorder. [ 18 ] A study by Goyal et al [ 19 ] was done on a total of 120 subjects on inflammatory markers in the first episode and bipolar mania. The results of the study supported the inflammatory pathophysiology of mania as shown by significantly higher values of neutrophil counts and neutrophil/lymphocyte ratio (NLR) and significantly lower values of lymphocyte counts in both the first episode and bipolar mania compared to healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, Bobi'nska et al [106] investigate the presence of MMPs (MMP-9, MMP-2, and MMP-7) and TIMP-2 in the blood of people experiencing depression. A pilot study conducted by Chandrasekaran et al [107] demonstrated, as its main finding, elevated serum levels of MMP-9 in patients diagnosed with bipolar disorder and a significant duration of suicidal thoughts.…”
Section: The Inflammatory Function Of Matrix Metalloproteinases In Hu...mentioning
confidence: 94%